Predictability of European winter 2016/2017. (4th November 2018) - Dunstone, Nick; Scaife, Adam A.; MacLachlan, Craig; Knight, Jeff; Ineson, Sarah; Smith, Doug; Thornton, Hazel; Gordon, Margaret; McLean, Peter; Palin, Erika; Hardiman, Steven; Walker, Brent
Abstract : Winter 2016/2017 was one of the driest on record for central Europe and the United Kingdom. This was the result of blocked atmospheric circulation with high pressure centred over North‐West Europe dominating the winter mean circulation pattern. Using large ensembles of simulated winters, we find that the observed winter 2016/2017 circulation was very similar in pattern and strength to the circulation associated with the top 10% of driest Central European winters. Here, we explore whether seasonal forecasts were able to predict this circulation pattern. Despite the fact that the observed circulation anomaly did not project on to the North Atlantic Oscillation (NAO), we find that forecasts starting in November did predict a high‐pressure anomaly over North‐Western Europe. We use two independent data sets, and methods, to probe the drivers of this circulation pattern. We find evidence for a Rossby Wave propagating out of the tropical Atlantic where there were anomalous local rainfall anomalies. This case study is another example of real‐time seasonal forecast skill for Europe and provides evidence for predictability beyond the NAO pattern. Abstract : European winter 2016/2017 was especially dry with parts of central Europe exceeding two SD s below climatology. This was driven by high pressure located over the North Sea that we show was predicted by seasonal forecasts starting in November. Further model analysis identifies large tropical Atlantic rainfall anomalies that appear to drive a Rossby wave‐train polewards and eastwards over Europe.